2013
DOI: 10.1080/09669760.2013.809656
|View full text |Cite
|
Sign up to set email alerts
|

The educational nature of different ways teachers communicate with children about natural phenomena

Abstract: This empirical study analyses the qualitatively different ways in which teachers approach children's learning in and about nature. The empirical data consists of video observations of children and teachers communicating with one another around natural phenomena found during excursions into a forest. Variation theory is presented as a framework for analysing the opportunities teachers provide for children's learning. The study identifies three qualitatively different ways in which teachers communicate with chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
0
29
0
8
Order By: Relevance
“…However, several Norwegian researchers have identified a need for more critical reflection on the pedagogical content of the time spent outside and question if simply being outdoors in itself is sufficient to meet the objectives in the curriculum concerning outdoor play and exploration (Kaarby & Tandberg, 2017;Moser & Martinsen, 2010;Skarstein, Berrefjord Ugelstad, & Grøsvik, 2018). Matters of concern have also been raised by Swedish researchers on early childhood (EC) teachers' abilities to recognise and fully facilitate the learning possibilities available outdoors, and particularly regarding the manners in which the teachers communicate with children about nature (Gustavsson & Pramling, 2014;Thulin, 2006;Thulin & Pramling, 2009). Gustavsson and Pramling (2014) point out that on nature excursions it seems that children are often left to make their own experiences and discoveries, although children also need assistance in order to notice different phenomena when learning about nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several Norwegian researchers have identified a need for more critical reflection on the pedagogical content of the time spent outside and question if simply being outdoors in itself is sufficient to meet the objectives in the curriculum concerning outdoor play and exploration (Kaarby & Tandberg, 2017;Moser & Martinsen, 2010;Skarstein, Berrefjord Ugelstad, & Grøsvik, 2018). Matters of concern have also been raised by Swedish researchers on early childhood (EC) teachers' abilities to recognise and fully facilitate the learning possibilities available outdoors, and particularly regarding the manners in which the teachers communicate with children about nature (Gustavsson & Pramling, 2014;Thulin, 2006;Thulin & Pramling, 2009). Gustavsson and Pramling (2014) point out that on nature excursions it seems that children are often left to make their own experiences and discoveries, although children also need assistance in order to notice different phenomena when learning about nature.…”
Section: Introductionmentioning
confidence: 99%
“…Matters of concern have also been raised by Swedish researchers on early childhood (EC) teachers' abilities to recognise and fully facilitate the learning possibilities available outdoors, and particularly regarding the manners in which the teachers communicate with children about nature (Gustavsson & Pramling, 2014;Thulin, 2006;Thulin & Pramling, 2009). Gustavsson and Pramling (2014) point out that on nature excursions it seems that children are often left to make their own experiences and discoveries, although children also need assistance in order to notice different phenomena when learning about nature. Furthermore, a study by Thulin (2006) showed that children's questions about nature were often answered by a counter question from the EC teacher or were simply left unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…(2009) tecken på en förskola med hög kvalitet. Lärares emellanåt förgivettagna förhållningssätt när det gäller barns tidigare erfarenheter kan försvåra barns lärande då läraren i kommunikation kring ett innehåll utgår från ett antagande om att barnet och läraren har samma tidigare erfarenhet istället för att försöka möta barnen utifrån hur de uppfattar innehållet (Gustavsson & Pramling, 2014).…”
Section: Förskolan Som En Miljö För Lärande Av Ett Innehållunclassified
“…Detta val har sin bakgrund i tidigare studier som fokuserat naturvetenskap i förskolan (Se t.ex. Fleer, 2009;Gustavsson & Pramling, 2014;Thulin, 2011). Dessa studier visar att förskollära-res inställning till sitt uppdrag i hög grad kommer att prägla de ramar för innehållets behandling och barns lärande som upprättas på den enskilda förskolan (Jfr.…”
Section: Kompetensutvecklingsinsatsens Designunclassified
“…Tanken er at antropomorfe uttrykksmåter gjør den naturvitenskaplige dialogen til lek og mer spennende for barna, selv om det er vist at barn som stiller naturvitenskapelige spørsmål ofte forventer naturvitenskapelige svar (Thulin, 2011). Det er også vist at barn som møtes med gode naturvitenskapelige forklaringer kan holde interessen mot fenomenet lenger enn de som møtes av antropomorfe uttrykksmåter (Gustavsson & Pramling, 2013). En mulig forklaring på bruk av antropomorfisering er mangel på faglig kunnskap, og at de er redd for at barnehagen blir for lik skolen (Thulin, 2011), men også barnehagelaerere med solid faglig bakgrunn kan bruke antropomorfe uttrykk (Gustavsson & Pramling, 2013).…”
Section: (1) 2017unclassified